2011
DOI: 10.1111/j.1365-2958.2011.07532.x
|View full text |Cite
|
Sign up to set email alerts
|

Rad52 function prevents chromosome loss and truncation in Candida albicans

Abstract: Summary RAD52 is required for almost all recombination events in S. cerevisiae. We took advantage of the heterozygosity of HIS4 in the C. albicans SC5314 lineage to study the role of Rad52 in the genomic stability of this important fungal pathogen. The rate of loss of heterozygosity (LOH) at HIS4 in rad52-ΔΔ strains was ~10−3, at least 100-fold higher than in Rad52+ strains. LOH of whole chromosome 4 or truncation of the homologue that carries the functional HIS4 allele was detected in all 80 rad52-ΔΔ His auxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 92 publications
6
50
0
Order By: Relevance
“…Chromosome homozygosis was long thought to be hampered in C. albicans by the presence of recessive lethal mutations dispersed throughout the genome. The existence of haploids (2), completely homozygous rad52-derived isolates (55), and partly homozygous diploid parasexual progenies (56) demonstrated that homozygosis of each one of the eight chromosomes can occur. Nevertheless, a bias in the homolog being retained was reported for certain chromosomes (2,55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome homozygosis was long thought to be hampered in C. albicans by the presence of recessive lethal mutations dispersed throughout the genome. The existence of haploids (2), completely homozygous rad52-derived isolates (55), and partly homozygous diploid parasexual progenies (56) demonstrated that homozygosis of each one of the eight chromosomes can occur. Nevertheless, a bias in the homolog being retained was reported for certain chromosomes (2,55).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of haploids (2), completely homozygous rad52-derived isolates (55), and partly homozygous diploid parasexual progenies (56) demonstrated that homozygosis of each one of the eight chromosomes can occur. Nevertheless, a bias in the homolog being retained was reported for certain chromosomes (2,55). This was the case for Ch4, one homolog of which could never be lost (2,55).…”
Section: Discussionmentioning
confidence: 99%
“…There is a slight, but reproducible difference in MMS sensitivity between CAI4-L and CAI4 ( Figure 9A). When we compare their SNP/CGH profiles, a homozygous region is evident on Chr2L in CAI4-L, whereas heterozygosity is maintained in CAI4 ( Figure 2B) Andaluz et al 2011). In CAI4-L, this LOH occurred via an interhomolog recombination event at coordinate 1,656,168 and we Figure 6 Proposed mechanisms for the generation of the several P strains (FOA R segregants) derived from URA3 transformants T6 and T7 as deduced from the SNP-CGH results.…”
mentioning
confidence: 84%
“…In this regard, some CAI4 stocks carry additional regions of LOH, such as CAI4-L, which has Chr2L long-range LOH and no detectable aneuploidy (Andaluz et al 2011). We cannot distinguish whether this long-range LOH was spontaneous or a result of unknown stress.…”
Section: Loss Of Heterozygosity In Candida Albicansmentioning
confidence: 95%
See 1 more Smart Citation